Genetic association of preeclampsia to the inflammatory response gene SEPS1 - Moses, Eric; Johnson, M.; Tømmerdal, L.; Forsmo, S.; Curran, J.; Abraham, L.; Charlesworth, J.; Brennecke, S.; Blangero, J.; Austgulen, R. (Mosby, Inc., 2008)
Objective: The objective of the study was to test for a genetic association between the G-105A promoter polymorphism of the inflammatory mediator Selenoprotein S (SEPS1) and preeclampsia. Study Design: A retrospective study in a large Norwegian case-control cohort compared maternal genotype and allele frequencies of the SEPS1 g.-105G>A polymorphism genotyped by SNPlex assay in preeclamptic (n = 1139) and control (n = 2269) women. Statistical significance was determined by ?2 and multivariate regression analyses. Results: Women with preeclampsia were 1.34 times more likely to have the GA or AA genotype (P = .0039; 95% confidence interval [CI] 1.09 to 1.64) and 1.22 times more likely to carry the A allele (P = .023; odds ratio, 1.22; 95% CI, 1.02 to 1.46). Conclusion: The A allele of the SEPS1-105G>A polymorphism is a significant risk factor for preeclampsia in this population. © 2008 Mosby, Inc. All rights reserved.